A MATHEMATICAL ANALYSIS of ZIKA VIRUS EPIDEMIC in RIO de JANEIRO AS A VECTOR-BORNE and SEXUALLY TRANSMITTED DISEASE - Cruz-Pacheco, Gustavo; Esteva, Lourdes; Ferreira, Claudia Pio [UNESP] (World Scientific Publishing, 2019)
In this work we formulate a mathematical model to assess the importance of sexual transmission during the Zika virus outbreak that occurred in Rio de Janeiro, Brazil, in 2015. To this end, we deduce from the model an analytical expression of the basic reproduction number of Zika, R0, in terms of the vectorial and sexual transmissions, and we use the estimations given in Ref. 1 [Villela DAM, Bastos LS, de Carvalho LM, Cruz OG, Gomes MFC, Durovni B, Lemos MC, Saraceni V, Coelho FC, Codeço CT, Zika in Rio de Janeiro: Assessment of basic reproduction number and comparison with dengue outbreaks, Epidemiol Infect 145(8):1649-1657, 2017] for the R0 values of Zika virus and dengue virus epidemics in Rio de Janeiro to evaluate the contribution of sexual transmission of Zika virus. According to the obtained results, sexual transmission (pure plus mediated by vector transmission) contributes from 23% to 46% for the R0 increment. Also, an asymmetric sexual transmission between men and women can explain the fact that the incidence of Zika virus in women was 60% higher than in man during the 2015 epidemics. We also carry out a sensitivity analysis using R0 as the output parameter. The results of this analysis have shown that the transmission rate between human and mosquito populations, the mosquito mortality rate, and the human infectious period are the parameters that contribute more to the R0 variation, highlighting the importance of vector control to halt disease transmission.
Keywords: Basic Reproductive Number; Ordinary Differential Equations; Sensitivity Analysis